Isolation of human monoclonal antibodies with neutralizing activity to a broad spectrum of SARS-CoV-2 viruses including the Omicron variants - Ueno, Mikako; Iwata-Yoshikawa, Naoko; Matsunaga, Akihiro; Okamura, Tadashi; Saito, Sho; Ashida, Shinobu; Yoshida, Isao; Nagashima, Mami; Asakura, Hiroyuki; Yaoita, Yuu; Suzuki, Jun; Sadamasu, Kenji; et al. (Antiviral research, 2022)
Monoclonal antibody therapy is a promising option for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and a cocktail of antibodies (REGN-COV) has been administered to infected patients with a favorable outcome. However, it is necessary to continue generating novel sets of monoclonal antibodies with neutralizing activity because viral variants can emerge that show resistance to the currently utilized antibodies. Here, we isolated a new cocktail of antibodies, EV053273 and EV053286, from peripheral blood mononuclear cells derived from convalescent patients infected with wild-type SARS-CoV-2. EV053273 exerted potent antiviral activity against the Wuhan wild-type virus as well as the Alpha and Delta variants in vitro, whereas the antiviral activity of EV053286 was moderate, but it had a wide-range of suppressive activity on the wild-type virus as well as the Alpha, Beta, Delta, Kappa, Omicron BA.1, and BA.2 variants. With the combined use of EV053273 and EV053286, we observed similar inhibitory effects on viral replication as with REGN-COV in vitro. We further assessed their activity in vivo by using a mouse model infected with a recently established viral strain with adopted infectious activity in mice. Independent experiments revealed that the combined use of EV053273 and EV053286 or the single use of each monoclonal antibody efficiently blocked infection in vivo. Together with data showing that these two monoclonal antibodies could neutralize REGN-COV escape variants and the Omicron variant, our findings suggest that the EV053273 and EV053286 monoclonal antibody cocktail is a novel clinically applicable therapeutic candidate for SARS-CoV-2 infection.